Narrativa, tradição, interculturalidade: os significados da formação acadêmica na identidade de jovens potiguara - Sousa, Elaine Freitas de (2017)
This thesis defends that subjects coming from a Potiguara cultural identity re-signifies their knowledge, built along their lifetime trajectory, through the knowledge and experiences leamed in the formative processes from their entrance into the university. Thus, to reflect about the experiences that involve this thesis, the theoretical references were constituted in the interrelation between several fields of knowledge and practice, such as university (Saviani 2007; Boaventura 2013); ethnicity and native identity (Hall 2006; Ianni 2004); multiculturalism, interculturalism and cultural studies (Candau 2008; Jovchelovitch 2011; Grando and Hasse 2001; Silva 2000; Brandão 2002). It includes Philosophy, Anthropology, Sociology and Education, highlighting the concept of identity as central category (Hall 2009; Bauman 2005; Silva 2013; Elias 1994; among others). Therefore, the general objective of this qualitative research was to investigate, from the life narratives of the native youths, the ways in which they re-signify their identity considering the academic experiences lived in the Executive Secretariat course, offered at campus IV of UFPB, in the Mamanguape Valley region. The specific objectives are: identify how the native students are inserting themselves into the academic universe; recognize fundamental subjects, spaces and processes so that these young people can build intersections between their cultural identities and the academic knowledge through an intercultural dialogue; perceive, from their lifetime trajectories, how their experiences could contribute to the entrance in the university and the choosing of a higher education programme. The methodological approach adopted was the (auto) biographical research because it allows the articulation of meanings from the centrality of narratives of the young Potiguara Natives, considering the concepts of experience (Larrosa 2002; Delory-Momberger 2006), training experience (Josso 2004) and narratives (Ricouer 1994; Benjamin 1994; Bertaux 2010). The procedure for the production of the narratives was a dialogical group (DG) with the participation of three native students, comprising the following activities: questionnaire application on personal, academic and professional information; practical activities for the development of the concepts underlying this thesis; and, lastly, the realization of the narrative. The participant observation, a roaming diary and the analysis of the academic reports of those involved complemented the data collection. We use the discursive textual analysis for the research corpus, under the bias of what Roque Moraes (2014) calls "a storm of light", because this methodology seeks to interpret the productions made and constructed in the qualitative research, representing a hermeneutic and heuristic understanding. Starting from the narratives, we understand moments and processes that made the subjects get involved in activities promoted by the university, seeking their insertion in that space. We also identified the subjects that allowed the intersection between their cultural identity and the academic knowledge, highlighting parents, relatives, friends and professors; and, lastly, we recognized some contradictions and complementarities existing in the intersection between academic and native knowledge, making possible a process ofre-signification of one's own identity.